Application of a film HPMC- paraffin on melon: effect on aromatics and activity of pectinmethylesterase - Esparza Rivera, Juan Ramón; Sierra Campos, Erick; Luna Zapién, Edén Areli; Minjares Fuentes, José Rafael; Reyes Avalos, Ma. Concepción; Meza Velázquez, Jorge Armando (Revista Mexicana de Ciencias Agrícolas, 2018)
The melon is a fruit appreciated for its aroma and flavor, but it has a short storage period. An alternative to extend this period is the use of edible films. In the present study the effect of the application of an edible film of hydroxypropylmethylcellulose-paraffin (HPMC-PAR) on aromatic components and the activity of melon pectinmethylteterase stored in refrigeration was evaluated. Cantaloupe melon fruits were covered with an edible film of HPMC-PAR and non-covered melons were taken as control. The melons were stored for 20 days at 8 ºC and 80% relative humidity. Every four days, the fruits were subjected to analysis of the concentration of ethylbutyrate, ethylcaproate, butylacetate, benzyl alcohol, methylbutanol and pectylmethylteterase activity (PME). The results showed that melons with film had a higher concentration of the analyzed esters, as well as a lower activity of PME compared to samples without film. However, the alcoholic compounds were not affected by the treatments. Therefore, the application of the film based on HPMC-paraffin promotes the increase of ester compounds during the first days of storage in refrigeration. In addition, the activity of PME can influence the amount of these aromatic compounds of the Cantaloupe melon pulp.